PEMBELAJARAN PENDIDIKAN AGAMA KRISTEN DI GEREJA SEBAGAI SARANA EFEKTIF DALAM PEMBENTUKAN KARAKTER JEMAAT TUHAN - Urbanus Sukri (Sekolah Tinggi Teologi Excelsius, 2021)
The congregation of God or the Church are people who are called out of this world into fellowship with Christ. The main vision of God's church present in the world is to be like Christ (Rom. 8:29; Gal. 4:19). To be like Christ, God's church must have the character of Christ in itself. The character of Christ is love, that is, love for God and neighbor. The efforts of church leaders so that the congregation has the character of Christ is by way of formation. There are many kinds and varieties of congregational building, including learning Christian Religious Education. Christian Religious Education is a modern term for discipleship that has been carried out by the servants of God in the Old Testament and preserved by the Lord Jesus in the New Testament. In the Bible, it has been proven that discipleship or Christian Religious Education has produced God's servants with character (loving God and others) in their day. It is concluded that the implementation of Christian Religious Education learning is the most effective development in shaping the character of Christ in the church of God in this modern era.Jemaat Tuhan atau Gereja adalah orang orang yang dipanggil keluar dari dunia ini masuk kedalam persekutuan bersama Kristus. Visi utama jemaat Tuhan hadir didunia adalah menjadi serupa dengan Kristus (Rm. 8:29; Gal.4:19). Untuk menjadi serupa dengan Kristus, jemaat Tuhan harus mempunyai karakter Kristus dalam dirinya. Karakter Kristus adalah kasih, yaitu kasih terhadap Allah dan sesama. Usaha para pemimpin jemaat agar para jemaat mempunyai karakter Kristus adalah dengan jalan pembinaan. Banyak macam dan ragam tentang pembinaan jemaat, diantaranya adalah pembelajaran Pendidikan Agama Kristen. Pendidikan Agama Kristen adalah istilah modern untuk pemuridan yang telah dilaksanakan oleh para hamba Allah di Perjanjian Lama dan dilestarikan oleh Tuhan Yesus di Perjanjian Baru. Didalam Alkitab, sudah terbukti bahwa pemuridan atau Pendidikan Agama Kristen telah menghasilkan para hamba Tuhan berkarakter (mengasihi Tuhan dan sesamanya) pada zamannya. Maka disimpulkan bahwa pelaksanan pembelajaran Pendidikan Agama Kristen adalah pembinaan yang paling efektif dalam pembentukan karakter Kristus jemaat Tuhan pada zaman modern ini.